Making the novel: Fiction and society in Britain, 1660-1789 - Hammond, Brean; Regan, Shaun (New York: Palgrave Macmillan, 2006)
Hammond and Regan advance a new cultural reading of the formation of the British novel. Rejecting a teleological narrative of the genre's rise, the study presents a dynamic picture of the emergence of the novel, that focuses upon formal innovation, social and cultural engagement, and artistic and commercial competition between authors. Containing in-depth analyses of over twenty novels, topics covered include amatory vs 'realist' fiction, anti-novel discourse, the Richardson-Fielding rivalry, Sterne and sentimental fiction, representations of Britain, and the formation of a national canon.